Table-like magnetocaloric effect around room temperature of antiperovskite composite materials based on Mn3Sn1-xGaxC. (June 2021) - Jiang, Congji; Yan, Jun; Wang, Xiangqian; Wei, Shijie; Liang, Pengli; Chen, Yunlin; Song, Yuzhe; Han, Genliang
Graphical abstract: Highlights: A nearly table-like magnetocaloric effect was obtained in the antiperovskite composite material. A new method was presented to design and synthesize practical composite magnetic refrigerants. The competition relationship between the operating temperature span and the maximal magnetic entropy change of the composite was clarified. Abstract: The Mn3 Sn1-x Gax C materials based on Mn3 SnC with Sn partially replaced by Ga were prepared and their phase transitions were studied. With increasing Ga content, the Curie temperatures ( T c ) of Mn3 Sn1-x Gax C gradually decrease, but the large phase transition entropy (Δ S ) is retained. Antiperovskite composite magnetic refrigerant was designed and synthesized by mixing the Mn3 Sn1-x Gax C materials with different phase transition temperatures. The composite presents a nearly table-like magnetic entropy change (-Δ S M )- T curve near room temperature. Compared with Mn3 SnC, the full width at half maximum (Δ T FWHM ) of (-Δ S M )- T curves of the composite increased from 5 K to 44 K, and the refrigerant capacity ( RCP ) increased from 27.1 J/kg to 58.67 J/kg at 5 Tesla (T). This composite material is beneficial to magnetic Ericsson cycle, providing a new method for developing practical magnetic refrigerants in antiperovskite compounds.